Hats in the ring : choosing Britain's Chief Rabbis from Adler to Sacks - Persoff, Meir (Judaism and Jewish life., 2013)
Prior to the latest Chief Rabbinical selection process, seven eminent rabbis were appointed to British Jewry's highest ecclesiastical post, although only six were installed and saw out their terms of office. The manner of their appointment was invariably coloured by intrigue, in-fighting and a host of other influences, not least an increasingly potent input by the dayanim of the London Beth Din, themselves not immune to strategic self-interest. Meir Persoff's scholarly yet accessible account of these seven appointments draws on a wealth of hitherto unaccessed and unpublished material, and on the stories of many of the protagonists involved, including in fascinating detail those who, by fair means and foul, failed to gain (or chose to reject) the coveted prize.